ANALISIS KINERJA KEUANGAN PT. PLN (PERSERO) INDONESIA PERIODE 2011-2015 - PURNAMA SARI, ITA (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2016)
The purpose of the research is to analyze the financial performance and financial health of PT. PLN (Persero) Indonesia in 2011- 2015 based on the Decree of the Ministry of State-Owned Enterprises No: KEP-100/MBU/2002 on company?s health assessment on eight indicators: ROE, ROI, Current Ratio, Cash Ratio, Collection Period, Inventories, Total Assets Turn Over, and Total Ratio of Own Capital to Total Assets and Trend Analysis. The result shows that the financial performance of the liquidity ratio indicates that the company has not fully settled its current debt by using cash and guarantee the current debt with current assets. Profitability ratio shows the company's financial performance has not fully generate profit by using its own capital and company assets. Leverage ratio shows that the company is able to finance the assets with its own capital and at the ratio of activity indicates that the company has been optimal in using the receivables and inventory to generate revenue but the total rotation of assets not yet optimal used to generate income. Therefore, the health assessment on the financial aspects of PT. PLN (Persero) Indonesia in the period of 2011-2015is predicated less healthy.